Skin manifestations of COVID-19 in a pregnant woman with premature rupture of membranes: A case report - Sri Sulistyowati; Nutria Widya Purna Anggraini (Faculty of Medicine, Universitas Islam Indonesia, 2021)
The number of COVID-19 cases, especially with pregnancy, remains a problem in the world and in Indonesia. The main clinical symptoms include fever (temperature >38°C), cough, and shortness of breath. In addition, it can be accompanied by fatigue, myalgia, gastrointestinal symptoms such as diarrhea, and even recently found manifestations of skin disorders. Skin manifestations in COVID-19 pregnant patients are still a rare condition. Skin manifestations can be an early sign of such infection, which therefore requires clinicians’ notice to allow them to conduct early COVID-19 screening in pregnant women for better outcomes of the mother and the baby. We present a 26-year-old primigravida at 39 weeks of gestational age with premature rupture of membranes and COVID-19 infection. Her complaints included itchy maculopapular rash and urticaria, then the pregnancy was terminated by a caesarean section, and the baby was born with good conditions. The skin lesions were given a mixture of corticosteroid cream and fusidic acid. The mother and the baby were discharged in a good condition.